2016
DOI: 10.1063/1.4963762
|View full text |Cite
|
Sign up to set email alerts
|

Efficient extraction of high power THz radiation generated by an ultra-relativistic electron beam in a dielectric loaded waveguide

Abstract: We have measured an intense THz radiation produced by a sub-picosecond, relativistic electron bunch in a dielectric loaded waveguide. For efficient THz pulse extraction, the dielectric loaded waveguide end was cut at an angle. For an appropriate choice of angle cut, such antenna converts the TM 01 mode excited in the waveguide into a free-space fundamental Gauss-Hermite mode propagating at an angle with respect to the electron beam trajectory. Simulations show that more than 95% of energy can be extracted usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 17 publications
(23 reference statements)
0
21
0
Order By: Relevance
“…In Eqs. (3,4). h < 0(respectively h > 0) means that higher energy (respectively lower energy) electrons are in the bunch head after the cavity, which leads to bunch lengthening (respectively shortening) (see (c) in Fig.…”
Section: Energy-chirped Beammentioning
confidence: 99%
See 1 more Smart Citation
“…In Eqs. (3,4). h < 0(respectively h > 0) means that higher energy (respectively lower energy) electrons are in the bunch head after the cavity, which leads to bunch lengthening (respectively shortening) (see (c) in Fig.…”
Section: Energy-chirped Beammentioning
confidence: 99%
“…Accelerator based sources of THz radiation have been proposed and developed at several laboratories worldwide [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. THz radiation, whose frequency range is from 0.1 THz (wavelength λ = 0.3 mm) to 30 THz (λ = 10 µm), is non-ionizing and has high transmission through non-metallic materials such as clothes, paper, and plastic.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-dielectric , bimetallic [26][27][28], and corrugated [29][30][31][32] structures have attracted strong interest for particle radiation, acceleration, and beam manipulation in the past decades. Dielectric loaded structures are promising for beam-based terahertz generation [6][7][8][9][10][11][12], two-beam acceleration [13][14][15][16], beam diagnostics [17], and beam manipulation [18][19][20][21]. Recently, it was demonstrated that the incorporation of a dielectric-lined waveguide located downstream of a photoinjector gun can provide a sufficient energy modulation from the self-wake to ballistically bunch a beam on a meter-scale footprint [22].…”
Section: Introductionmentioning
confidence: 99%
“…One of beam-based methods is using a metallic beam pipe with small corrugation [6,7]. DWA structures are also considered as promising candidates for generation of radiation in the Terahertz range [5,[8][9][10][11][12]. It is notable that direct experimental observation of wakefield effects in a THz regime was performed in a planar diamond accelerating structure [13] and in a cylindrical dielectric-lined waveguides with the use of tubes fabricated from fused silica [14] and chemical-vapor deposition diamond [15].…”
Section: Introductionmentioning
confidence: 99%